Determinants of foodservice satisfaction for patients in geriatrics/rehabilitation and residents in residential aged care. (16th September 2011) - Wright, Olivia R. L.; Connelly, Luke B.; Capra, Sandra; Hendrikz, Joan
Abstract Background Poor satisfaction with institutional food is a significant moderator of food intake in geriatrics/rehabilitation and residential aged care. Purpose To quantify the relationship between foodservice satisfaction, foodservice characteristics, demographic and contextual variables in geriatrics/rehabilitation and residential aged care. Methods The Resident Foodservice Satisfaction Questionnaire was administered to 103 patients of 2 geriatrics/rehabilitation units and 210 residents of nine residential aged care facilities in Brisbane, Australia. Ordered probit regression analysis measured the association of age, gender, ethnicity and appetite, timing and amount of meal choice, menu selectivity, menu cycle, production system, meal delivery system and therapeutic diets with foodservice satisfaction. Results Patient and resident appetite (P < 0.01), the amount and timing of meal choice (P < 0.01), self‐rated health (P < 0.01), accommodation style (P < 0.05) and age (P < 0.10) significantly moderated foodservice satisfaction. High protein/high energy therapeutic diets (P < 0.01), foodservice production (P < 0.01) and delivery systems (P > 0.01) were significant moderators for those with 'fair' self‐rated health. Conclusions Patient and resident characteristics and structural and systems‐related foodservice variables were more important for influencing foodservice satisfaction than characteristics of food quality. The results suggest modifications to current menu planning and foodservice delivery methods: reducing the time‐lapse between meal choice and consumption, augmenting the number of meals at which choice is offered, and revising food production and delivery systems.It is important that residents in poorer health who are a high risk of under‐nutrition are provided with sufficient high protein/high energy therapeutic diets. Diets that restrict macro‐ and micro‐nutrients should be minimized for all patients and residents.